AN INVESTIGATION OF STUDENTS’ WILLINGNESS TO COMMUNICATE IN SPEAKING CLASS IN ONLINE LEARNING - Zati Dillah Idzni; Wawan Setiawan (PROJECT (Professional Journal of English Education), 2021)
This study aims to investigate students’ willingness to communicate (WTC), the factors influencing students became reluctant to communicate, and teachers’ strategies to encourage students to be willing to communicate. The research was conducted in speaking class during the synchronous online learning. The data were collected from questionnaires and semi-structured interviews, so the mixed methods were employed. The respondents of this study were 25 students of eighth graders at SMPN 69 Jakarta. The results show that the students had low level of willingness to communicate, there were four factors influencing students become reluctant to communicate (self-confidence, anxiety, motivation, students’ personalities, and situational variables), and three strategies that the teachers employed to encourage students to be willing to communicate in speaking class such as playing games, using technology, and providing a variety of interactional activities. Keywords:  Willingness to Communicate, Online Learning, Strategies